Unified System for Processing Non-Personalized Data - A. V. Brezhnev; E. Z. Gukov (Открытое образование (Москва))
The purpose of the study. The purpose of this article is to study the possibility of creating a unified register of non-personalized data, that is, data that cannot be attributed to a specific subject of personal data. The objective of the study is to analyze relevant materials for the purpose of the study, to determine the need for this system, to determine possible areas of application of the system, to determine the system sources and data on which the system can be based. The object of the study is a unified system for processing non-personalized data, the issue of creating this system and the opportunities that open up to the user.The subject of the study is the question of the data that can be processed in this system, as well as the section in which the data can be interpreted.Research methods. The article uses the following research methods: analysis of open data sources, modeling of the target solution in the form of a concept.Results. The article presents an example of the implementation of a system for processing non-personalized data. The variants of systems that currently have a set of data on personal data subjects and are ready to conduct a preliminary scoring analysis are presented. A possible result of the application of scoring is presented, using the example of the banking industry. An analysis of the current state of citizens' data processing systems was carried out. The results of the analysis showed that currently there is no single system that would allow for scoring analysis on the subject of personal data, aggregating data from various sources of state systems. There are no data in open sources on the progress of the development of a system that allows for scoring analysis based on non-personalized data. At the same time, the creation of a unified system for processing non-personalized data can both have a positive impact on the economic indexes of consumers connected to it, and contribute to the implementation of strategic plans of the state.Conclusion. During the study, a project was proposed for implementation to create a unified system for processing non-personalized data. A variant of data that can be used for primary scoring is proposed. The advantages of this system include a positive economic effect for organizations connected to the system, due to the reduction of monetary losses, improving the quality of sales, increasing customer loyalty, for the state, a positive effect can be an increase in the transparency of citizens' data and a decrease in the number of economic crimes, for citizens, the positive side of the system is to reduce information noise, due to a decrease in the number of studies from the companies, reduction of fraudulent actions, in relation to consumers. The disadvantages of the system include a high risk of data leakage, as a result of an increase in the number of crimes, incorrect interpretation of data by the scoring model, unavailability of various services for clients of organizations due to lack of data, the risk of data misuse by the operator of personal data processing. As a result, we can conclude that with the proper level of user data protection and clear rules for working with data, this system has good prospects for achieving the economic goals of both private companies and the state.